PENDAMPINGAN PENERAPAN STRATEGI PEMBELAJARAN INOVATIF DALAM IMPLEMENTASI KURIKULUM 2013 - Gunawan, Imam; Ulfatin, Nurul; Sultoni, Sultoni; Sunandar, Asep; Kusumaningrum, Desi Eri; Triwiyanto, Teguh (ABDIMAS PEDAGOGI, 2017)
Abstract: Management of effective learning aspects will encourage students to participate actively during the learning process. There is no appropriate learning strategy for all learning materials and situations as well as supporting the achievement of learning objectives. Teacher variation in applying learning strategy becomes important thing done in learning activity. The target audience for the implementation of innovative learning strategies in the implementation of Curriculum 2013 are the teachers of Private Madrasah Ibtidaiyah (Madrasah Ibtidaiyah Swasta / MIS) Lowokwaru Malang. Activities will be held in one of the MI Al Fattah classrooms, with a target audience of 17 teachers. The method used is varied discourse and practice (peer teaching). The results of this mentoring activities include several components, namely: (1) the success of the target number of mentoring participants in attendance were 17 teachers (85%) of the total invited as many as 20 teachers; (2) the achievement of the material targets given to the mentoring participants, and also additional knowledge on the implementation of lesson study for teachers; and (3) outcome achievement of mentoring activities, namely lesson plan (RPP) based on cooperative learning model compiled by teacher and display video of teacher teaching in implementing learning activities by applying cooperative learning model.Keywords: mentoring, learning strategy, Curriculum 2013Abstrak: Pengelolaan aspek pembelajaran yang efektif akan mendorong siswa berpartisipasi secara aktif pada saat proses pembelajaran. Tidak ada strategi pembelajaran yang tepat untuk semua materi dan situasi pembelajaran serta menunjang ketercapaian tujuan pembelajaran. Variasi guru dalam menerapkan strategi pembelajaran menjadi hal yang penting dilakukan dalam kegiatan pembelajaran. Khalayak sasaran kegiatan pendampingan penerapan strategi pembelajaran inovatif dalam implementasi Kurikulum 2013 ini adalah para guru MIS Kecamatan Lowokwaru Kota Malang. Kegiatan akan dilaksanakan di salah satu ruang kelas MI Al Fattah, dengan jumlah khalayak sasaran adalah 17 orang guru. Metode yang digunakan adalah ceramah bervariasi dan praktik (peer teaching). Hasil kegiatan pendampingan ini mencakup beberapa komponen, yaitu: (1) keberhasilan target jumlah peserta pendampingan yang hadir yakni 17 orang guru (85%) dari total yang diundang sebanyak 20 orang guru; (2) ketercapaian target materi yang diberikan kepada peserta pendampingan, dan juga ada tambahan pengetahuan tentang implementasi lesson study bagi guru; dan (3) ketercapaian luaran kegiatan pendampingan, yakni RPP berbasis model pembelajaran kooperatif yang disusun oleh guru dan video tampilan mengajar guru dalam melaksanakan kegiatan pembelajaran dengan menerapkan model pembelajaran kooperatif.Kata kunci: pendampingan, strategi pembelajaran, Kurikulum 2013